Becoming a permanent member of the UN Security Council - Ulrich Schneckener (Stiftung Wissenschaft und Politik (SWP), 2005)
With the submission of the report of the 'High Level Panel on Threats, Challenges and Change,' the critical phase for the reform of the United Nations has begun. The focus is on changing the composition of the UN Security Council by expanding its member-ship. The High Level Panel considers this to be imperative in order to put the UN in a better position to address the security challenges identified in the report. The first steps are expected during the forthcoming months: The so-called 'G-4' (Germany, Japan, Brazil and India), following the presentation of the report of UN Secretary-General Kofi Annan, expected in March, will most likely submit the question of enlargement to the vote of the General Assembly. The timing and exact details of this move are still open. Against this background, the key questions are: what are the prospects for the German candidacy? What requirements and demands will German foreign policy be confronted with? (SWP-Comments / SWP)
Keywords: 320